A case study of product-service integration for train braking systems - Shihundla, Bongani Trevor; Mpofu, Khumbulani; Adenuga, Olukorede Tijani (Cranfield University)
A product service system requires coordinated approach from multiple stakeholder groups. Industry, government, and civil society must work together to create and promote the deployment and smooth operation of these systems for a more sustainable economy. The train braking system problem areas such as failure detection, big data collection and sensor-based degradation monitoring have created opportunities for researchers to create jobs in the service sector. The paper aims to design product-service integration train braking system as a big data component with combination of dataset, volume, speed, and data diversity. The big data potentials and analysis using “V” model for train brakes integration and ishikawa diagram for the electro-pneumatic brake system that is applicable to the railcar brakes manufacturing industries fuse railcar’s sensory components innovation to market. This is where advanced analysis to examine the available data and organize it using advanced visualization techniques.
11th International Conference on Through-life Engineering Services - TESConf 2022, 8-9 November 2022, Cranfield UK
Keywords: Product Service System; Internet of Things; Servitisation; FMEA; Sensors; Integration